Multisectoral cooperation in cases of domestic violence from the point of view of the social work centre - Čvorović, Dragana; Otašević, Božidar; Vranešević, Milena (Sociološki pregled, 2021)
The aim of this research was to determine the current state of multisectoral cooperation between the competent state bodies and institutions provided by the Law on Prevention of Domestic Violence, recognized as a basis for preventing domestic violence and providing protection and support to victims. The empirical findings were obtained by surveying 43 employees in the social work centres in the Srem administrative district, who act in cases of domestic violence. After data collection, they had to be organized, so the statistical method of descriptive statistics was applied and for that purpose, the statistical software package SPSS was used (ver. 20). The results of the research showed the efficiency of mutual cooperation between the competent authorities, but also the necessity of continuing the work on the reform of the above-mentioned legal text.
Keywords: multisectoral cooperation; domestic violence; social work centre; Law on Prevention of Domestic Violence